A World of a Thousand Independent Regions: Confronting the Ever-Increasing Refugee Problem - Neis, Hans Joachim; Chaiwat, Pamanee (Urban planning, 2023)
Based on Pattern 1 “Independent Regions” in the book A Pattern Language by Alexander et al. (1977), we investigate a fundamental socio-spatial alternative for reorganizing our world, countries, and metropolitan regions. When put into the context of large worldwide problems, such as climate change, nuclear danger, pandemics, overpopulation, and refugee crises, the innovative idea of “independent regions” presents itself as a promising alternative to the current imbalance of few large and dominant countries in contrast to a wide majority of smaller and medium-sized countries. Working on the development of a refugee pattern language (RPL), this alternative can help to solve larger worldwide problems including the human-made refugee problem. In RPL pattern “3.2 A World of Independent Regions,” we explore this bottom-up alternative based on fundamental principles with an ideal population size for governing itself democratically and equity among regions in a world community. Other considerations include the potential to reduce the root problem of refugee creation of big countries vs. small counties, in cooperation with independent regions, and world regions. Updating this concept involves considering suggestions and new ideas that might make the outcome richer in overlaps, assembly, and scope. The relevance and vision of this concept and pattern are probably most visible and needed in the current turmoil of a transforming world.